Tissue engineering as a remarkable tool for cartilage repair - Silva, M. L. Alves da (2013)
Articular cartilage is a very specialized tissue with outstanding load-bearing capacity. It consists mainly of a dense extracellular matrix (ECM) with chondrocytes embedded on it. Cartilage has very low capacity of self-repair and regeneration after traumatic, degenerative or inflammatory injury. Current available surgical treatments for cartilage repair present several drawbacks, such as possible implant rejection or infection, or the need for revision after some years of implantation. Autologous chondrocyte implantation (ACI) is an autologous therapy that was proposed as a basis for tissue engineering strategies to repair cartilage (1). Modifications on various aspects of this surgical technique have been developed, comprising the use of natural-based scaffolds as supports for chondrocyte expansion (2). Many strategies and systems have been developed along the years for cartilage regeneration and repair. Scaffolds play a major role in those strategies, as they provide the support for cell growth and to promote extracellular matrix production. Both natural based (3) or synthetic scaffolds (4) have been successfully used as supports for chondrogenic differentiation or cartilage-like tissue production. The interest in cells cross-talk and communication has been growing in the past years, revealing that signalling pathways are pivotal elements when understanding the tissue formation and its repair mechanisms (5). Chondrocytes release morphogenetic signals that influence the surrounding cells, for example, stem cells, to differentiate into the chondrogenic lineage (5). In fact, the increased cartilage formation on co-cultures using stem cells and articular chondrocytes has been reported (6). Therefore, the study of co-cultures using chondrocytes and undifferentiated cells is a very promising strategy to develop engineered cartilage.